Delamination and chip breaking mechanism of orthogonal cutting CFRP/Ti6Al4V composite. (January 2022) - Fu, Qiang; Wu, Shujing; Li, Changhe; Xu, Jinyang; Wang, Dazhong
Abstract: The CFRP/Ti6Al4V composite has excellent properties of CFRP and Ti6Al4V. Therefore, they are widely used in aerospace and some military fields. The laminated structure of CFRP/Ti6Al4V composite is different from the traditional homogeneous workpiece, and the properties of each layer are diverse, so the processing performance is poor. The experimental research cost of CFRP/Ti6Al4V composites is relatively high and has certain limitations. The finite element method is a promising alternative. In the research, a finite element model combining the macro and micro with the fiber orientation of 90° was established. By combining the mechanism of exit burr formation in the cutting direction of Ti6Al4V and the delamination mechanism of CFRP composites, a new mechanical model was proposed for CFRP/Ti6Al4V composites during this study, and it was found that there is not a linear relationship between the rake angle and the delamination of CFRP/Ti6Al4V composites during the cutting process. The results show that the delamination damage of CFRP/Ti6Al4V composites is serious when the rake angle is 4° 10°. The delamination damage is light when the rake angle is 0° 4°. And the delamination damage is the smallest when the rake angle is 10° 20°. In the cutting process, the tremor of the Ti6Al4V phase is also an important factor for delamination. During the extrusion of Ti6Al4V relative to the CFRP phase, the fragmentation of the epoxy matrix leads to brittle fracture of the carbon fibers and shear damage can occur. The brittle fracture height is minimum when the rake angle is 16°. The shear damage height is minimum when the rake angle is 10°. The tremor of Ti6Al4V phase is also an important factor for delamination damage. The fracture of the epoxy resin matrix leads to brittle fracture and shear damage of carbon fiber. The brittle fracture height has a linear relationship with the fracture height of epoxy resin. When the cutting sequence is CFRP → Ti6Al4V, a better surface quality can be obtained, effectively avoiding carbon fiber brittle fracture. Therefore, the rake angle and cutting sequence are of great importance for processing CFRP/Ti6Al4V composites. Therefore, it is of reference significance for the machining of 90° fiber orientation.